2004
DOI: 10.1093/nar/gkh258
|View full text |Cite
|
Sign up to set email alerts
|

The genome sequence of Bacillus cereus ATCC 10987 reveals metabolic adaptations and a large plasmid related to Bacillus anthracis pXO1

Abstract: We sequenced the complete genome of Bacillus cereus ATCC 10987, a non-lethal dairy isolate in the same genetic subgroup as Bacillus anthracis. Comparison of the chromosomes demonstrated that B.cereus ATCC 10987 was more similar to B.anthracis Ames than B.cereus ATCC 14579, while containing a number of unique metabolic capabilities such as urease and xylose utilization and lacking the ability to utilize nitrate and nitrite. Additionally, genetic mechanisms for variation of capsule carbohydrate and flagella surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
266
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(285 citation statements)
references
References 77 publications
17
266
0
2
Order By: Relevance
“…To assess the mammalian virulence of B. cereus G9241, A͞J mice were challenged by i.p. injection (21) with mature spores of B. anthracis Sterne, B. cereus G9241, and B. cereus ATCC10987 (12). In these preliminary studies, G9241 produced 100% lethality, consistent with the positive control B. anthracis Sterne, although lethality was achieved faster when the high-spore dose was inoculated (t test, P ϭ 0.081) (Fig.…”
Section: Isolation Of B Cereus G9241 During a Retrospective Analysimentioning
confidence: 53%
See 2 more Smart Citations
“…To assess the mammalian virulence of B. cereus G9241, A͞J mice were challenged by i.p. injection (21) with mature spores of B. anthracis Sterne, B. cereus G9241, and B. cereus ATCC10987 (12). In these preliminary studies, G9241 produced 100% lethality, consistent with the positive control B. anthracis Sterne, although lethality was achieved faster when the high-spore dose was inoculated (t test, P ϭ 0.081) (Fig.…”
Section: Isolation Of B Cereus G9241 During a Retrospective Analysimentioning
confidence: 53%
“…Although genomic sequences with homology to B. anthracis pXO1 and pXO2 sequences have been detected in other Bacillus spp. (12), this work reports on the toxin genes and an entire pXO1-like plasmid found outside of a B. anthracis isolate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the B. cereus group has received much attention in the past few years and many B. cereus group genomes have recently been sequenced and published (Han et al, 2006;Ivanova et al, 2003;Rasko et al, 2004;Read et al, 2002Read et al, , 2003, hardly any research has been done on TCSs in this bacterial group. Only recently, a number of HKs has been shown to initiate sporulation in B. anthracis (Brunsing et al, 2005) and a RR has been shown to activate the alternative sigma factor s B in B. cereus (van Schaik et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the sequence data of phaR was 484 bp and the BLAST search of homologous sequence to PHAR showed 99% homology to PHA synthase subunit PHAR; regulator of PhaP of Bacillus cereus ATCC 10987, accession No. : NC_003909.8 [22] and Bacillus thuringiensis serovar finitimus YBT-020, accession No. : NC_017200.1.…”
Section: Discussionmentioning
confidence: 99%